Administrative Modernization and Literacy Policy Implementation in School Library Governance - Rohmanur Mala; Siti Atwano Pisriwati; Deny Hadi Siswanto (Pustaka Bangsa Indonesia, 2026)
This study aims to evaluate the comprehensive library management system, automation evolution, and literacy policies at SMA Muhammadiyah Mlati. Employing a qualitative case study design, this research gathered data from purposively selected informants, including library management, technical staff, and school administrators. Data collection was structured through semi-structured interviews, direct physical observations, and a critical documentation review, validated via data source triangulation. The findings reveal that the library successfully transformed into a well-regulated, digitally advanced learning hub. Key operational milestones include the strategic enforcement of visualized rules, administrative modernization through SLiMS application automation, professional collection curation utilizing the Dewey Decimal Classification system, and deliberate infrastructure zoning for diverse learning modalities. Furthermore, the library acts as an active catalyst for school-wide literacy programs and academic collaboration. Despite these achievements, chronic infrastructural limitations persist, particularly the absence of self-service catalog terminals and optimized climate control. Therefore, this study highly recommends that school management invest in Online Public Access Catalog terminals, upgrade centralized climate control systems, and allocate dedicated funding for ongoing facility expansion to meet 21st-century educational standards